Valorization of Imidazolium-Based Salts as Next-Generation Antimicrobials: Integrated Biological Evaluation, ADMET, Molecular Docking, and Dynamics Studies - Merimi, Chaimae; Benabbou, Abdessamad; Fraj, Elmehdi; Khibech, Oussama; Yahyaoui, Meryem Idrissi; Asehraou, Abdeslam; Messali, Mousslim; Harrad, Mohamed Anouar; Challioui, Allal; Bouammali, Boufelja; Touzani, Rachid; Hammouti, Belkheir; Almutairi, Saud M. (Universitas Pendidikan Indonesia (UPI), 2026)
This study aimed to investigate the antimicrobial potential of four imidazolium-based salt derivatives (A1–A4) using an integrated approach that combined in vitro biological assays with computational analysis. The compounds were screened against various Gram-positive and Gram-negative bacteria, as well as fungal strains, while computational methods like ADMET predictions and molecular simulations assessed their viability and mechanism. The results revealed that compounds A3 and A4 possess potent antibacterial activity comparable to gentamicin, particularly against E. coli, with A3 also showing significant antifungal efficacy. These findings were strongly supported by computational analysis, which predicted favorable oral bioavailability, acceptable toxicity, and confirmed a stable binding interaction with the bacterial enzyme DNA gyrase. The primary implication is the identification of A3 and A4 as promising therapeutic candidates for developing new antimicrobials to combat drug-resistant pathogens, validating this integrated research strategy for future drug discovery.